Penanaman Nilai Pendidikan Karakter Kedisiplinan Dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Umi Hanik, Elya; Nur Hanifah , Afnan; Istiqomah, Nalimatul; Trisnawati, Wahyu; Syifa, Layyinatus (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
Students must be able to improve academic results and character. Therefore, teachers have a vital responsibility in instilling discipline in their students. This writing aims to learn about implementing the inculcation of disciplinary character values in improving student learning outcomes. This research uses descriptive qualitative research methods. This study collected data through interviews, observation, and documentation. Data collection was carried out in discussion forums with foundations, principals, and teachers to obtain information about applying discipline character values in improving student learning outcomes with various school policies at Al-Masoem Elementary School through a question-and-answer process. To explain the process of instilling disciplinary character values that can improve student learning outcomes. The population of this study was students and educators of SD AL-Ma'soem. The study results concluded that the values of disciplined characters were obtained consistently through time and materials that could help students achieve their potential. This study is inseparable from the teacher's responsibility in developing student character through life habits, discipline, attitudes, behavior, and ethics. Thus, the availability of this paper is believed to be able to instill discipline in children, improve learning outcomes.